Derivatives markets and analysis - Johnson, R. Stafford (Bloomberg financial series., 2017)
"A practical, informative guide to derivatives in the real world Derivatives is an exposition on investments, guiding you from the basic concepts, strategies, and fundamentals to a more detailed understanding of the advanced strategies and models. As part of Bloomberg Financial's three part series on securities, Derivatives focuses on derivative securities and the functionality of the Bloomberg system with regards to derivatives. You'll develop a tighter grasp of the more subtle complexities involved in the evaluation, selection, and management of derivatives, and gain the practical skillset necessary to apply your knowledge to real-world investment situations using the tools and techniques that dominate the industry. Instructions for using the widespread Bloomberg system are interwoven throughout, allowing you to directly apply the techniques and processes discussed using your own data. You'll learn the many analytical functions used to evaluate derivatives, and how these functions are applied within the context of each investment topic covered. All Bloomberg information appears in specified boxes embedded throughout the text, making it easy for you to find it quickly when you need or, or easily skip it in favor of the theory-based text. Managing securities in today's dynamic and innovative investment environment requires a strong understanding of how the increasing variety of securities, markets, strategies, and methodologies are used. This book gives you a more thorough understanding, and a practical skillset that investment managers need. Understand derivatives strategies and models from basic to advanced Apply Bloomberg information and analytical functions Learn how investment decisions are made in the real world Grasp the complexities of securities evaluation, selection, and management The financial and academic developments of the past twenty years have highlighted the challenge in acquiring a comprehensive understanding of investments and financial markets. Derivatives provides the detailed explanations you've been seeking, and the hands-on training the real world demands"--